Metaverse or Urban Digital Twin: That is the Question - Romano Fistola; Ida Zingariello (img journal, 2024)
The growing interest in the Metaverse from the business world is a testament to its increasing importance and the potential impact it could have on our society. Large companies and investors have recognized the enormous economic potential that the Metaverse can offer, prompting them to invest significant amounts of money in its growth and the development of platforms and applications. The acquisition of land and properties in the Metaverse by prominent figures in various sectors, such as finance, entertainment, and sports, reflects the rise of the Metaverse as a new form of expression, entertainment, and social interaction. Bringing these reflections into the field of urban planning, we can say that the technological innovation behind the development of the Metaverse has dematerialised the urban object by transfiguring it into an immaterial digital content. Can new technologies merely replicate or simulate the city? Starting from this question, this paper seeks to overcome a naive fascination with the Metaverse, proposing instead a reflection on the Urban Digital Twin and the Augmented City, in the firm belief that new technological tools can redefine and develop new dimensions of humanised space rather than reproduce a simulacrum of the city inhabited by cyber-citizens.